Four Dogmas of Environmental Economics. (1st November 1994) - Sagoff, Mark
Abstract : Four dogmas have shaped modern neoclassical economics. The first proposes that markets may fail to allocate resources efficiently, that is, to those willing to pay the most for them. The second asserts that choices, particularly within markets, reveal preferences. The third is the assumption that people always make the choices they expect will benefit them or enhance their welfare. The fourth dogma holds that perfectly competitive markets will allocate resources to their most beneficial uses. This is the doctrine of the invisible hand. I argue that these dogmas of applied welfare economics should be abandoned. One consequence of doing so will be an increased interest in the institutional context of production. A second will be a turn toward empiricism.